2012
DOI: 10.1007/s12035-012-8233-5
|View full text |Cite
|
Sign up to set email alerts
|

The Shortest Isoform of Dystrophin (Dp40) Interacts with a Group of Presynaptic Proteins to Form a Presumptive Novel Complex in the Mouse Brain

Abstract: Duchenne muscular dystrophy (DMD) causes cognitive impairment in one third of the patients, although the underlying mechanisms remain to be elucidated. Recent studies showed that mutations in the distal part of the dystrophin gene correlate well with the cognitive impairment in DMD patients, which is attributed to Dp71. The study on the expression of the shortest isoform, Dp40, has not been possible due to the lack of an isoform specific antibody. Dp40 has the same promoter as that found in Dp71 and lacks the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 33 publications
(36 reference statements)
0
37
0
1
Order By: Relevance
“…Considering the fact that Dp427 and the other Dp isoforms, including Dp71, are localized beneath the plasma membranes of muscle and/or neuronal cells by interacting with dystroglycan-related molecules [5][6][7][8]15], it is possible that common molecular mechanisms will be involved in the Dp40 localization. However, we previously showed that Dp40 is not likely associated with membrane-spanning glycoproteins [14], suggesting that a particular molecular mechanism different from that related to dystroglycan-related molecules might be responsible for the Dp40 localization. Thus, we must consider the question, ''What kinds of molecules are responsible for the Dp40 localization?''…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Considering the fact that Dp427 and the other Dp isoforms, including Dp71, are localized beneath the plasma membranes of muscle and/or neuronal cells by interacting with dystroglycan-related molecules [5][6][7][8]15], it is possible that common molecular mechanisms will be involved in the Dp40 localization. However, we previously showed that Dp40 is not likely associated with membrane-spanning glycoproteins [14], suggesting that a particular molecular mechanism different from that related to dystroglycan-related molecules might be responsible for the Dp40 localization. Thus, we must consider the question, ''What kinds of molecules are responsible for the Dp40 localization?''…”
Section: Discussionmentioning
confidence: 88%
“…The amino acid sequence used for the antigen is totally included in full-length Dp (also known as Dp427) and a short isoform of Dp, Dp71 (Fig. 1A) [6,14]. To validate the reactivity of the anti-Dp40 antibody, anti-Dp40, antiDp71, or control IgG immunoprecipitations were performed using adult mouse cerebrum followed by Western blotting with the anti-Dp40 antibody, showing that the anti-Dp40 antibody was able to immunoprecipitate and detect both Dp40 and Dp71 proteins (Fig.…”
Section: Expression Profile Of Dp40 Protein In the Mouse Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue distribution of the Dp40 transcript is similar to that of Dp71 and it is also expressed in early development and in murine ES cells [4]. Previously, the expression of Dp40 protein in the mouse brain and its interaction with a group of presynaptic proteins was reported [5]. Recently, somatodendritic and nuclear localization of Dp40 wild type, in cultured mouse hippocampal neurons, has been shown and function for this protein in neuronal maturation and postsynaptic processes has been proposed [6].…”
Section: Q2mentioning
confidence: 89%
“…Some results suggest that most of the alterations associated with cognitive impairment are related to mutations of the specific dystrophin isoforms Dp140 and Dp71 (Moizard et al, 1998(Moizard et al, , 2000. Further studies suggest the possible involvement of other isoforms (Giliberto et al, 2004;Taylor et al, 2010;D'Angelo et al, 2011;Tozawa et al, 2012). A variety of studies have focused their attention mainly on the disruption of neuronal function, yet there is evidence that some brain functions (such as working and reference memory) are not compromised despite the lack of dystrophin (Sesay et al, 1996;Vaillend et al, 1998;Hinton et al, 2007).…”
Section: Introductionmentioning
confidence: 99%